The Action - Reflection - Modelling (ARM) pedagogical approach for teacher education : a Malaysia-UK project - Jarvis, Joy; Dickerson, Claire; Thomas, Kit; Graham, Sally (The Australian journal of teacher education, 2014)
This article presents the Action - Reflection - Modelling (ARM) pedagogical approach for teacher education developed during a Malaysia-United Kingdom (UK) collaborative project to construct a Bachelor of Education (BEd) (Honours) degree program in primary mathematics, with English and health and physical education as minor subjects. The degree program was written collaboratively by teacher educators in two Institutes of Teacher Education in Malaysia and in the University of Hertfordshire, UK, to meet the requirements for training Malaysian school teachers to teach in Malaysian schools. A cohort of 120 students studied the program full-time over four years, graduating in 2010. The three principles of the ARM approach were chosen to underpin the learning and teaching for the program. These principles highlight the role of active participation and active learning on the part of the learner; the value of reflective learning and reflection for both student teachers and pupils; and modelling by staff to student teachers and by student teachers to pupils in school. The approach was aligned with the curriculum specifications for mathematics in primary schools in Malaysia, which emphasised components of active learning. This article explains how the ARM approach was developed, shared and used during the BEd degree program; provides the rationale for selecting the three principles; and describes the research methods used to explore the views and experiences of program participants. Some findings from the research are presented, drawn from a dataset that comprises survey responses from more than 180 participants: Malaysian senior managers, teacher educators, student teachers and school mentors. The findings are discussed in the context of using ARM in teacher education and in primary schools in Malaysia, and of implementing change in learning and teaching. Throughout this project the teacher educators from Malaysia and the UK engaged in dialogue about their professional practice and learnt about the personal, professional and cultural values and beliefs that shaped the pedagogies of both parties and of the individual practitioners. The value of articulating pedagogy as a means of developing practice endorses the views of others with expertise in this area who stress the importance of making pedagogies explicit in teacher education and has implications for the practice of student teachers and teacher educators. [Author abstract, ed]